Analisis Kualitas Instrumen Tes Kognitif pada Program Islamisasi Ilmu Pengetahuan (Pendekatan Teori Tes Klasik): Analysis Of The Quality Of Cognitive Test Instruments In The Islamization Of Science Program (Classical Test Theory Approach) - Taufik Rizki Sista; Ulfatun Wahidatun Nisa (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2024)
This study aims to analyze the quality of cognitive test instruments in the science Islamization program at Darussalam Gontor University. This type of research is descriptive quantitative with a classical test theory analysis approach that tests the level of difficulty, discriminating power and deceptive power of each question. The sample was 50 students who randomly participated in the science Islamization program. Researchers use the ITEMAN application to analyze question items. The analysis showed that of the ten questions tested, there was 1 question that was coded to be eliminated, 1 question passed without revision, and eight suggested revising some multiple-choice answer items. The alpha conbrach score shows a score of 0.5, which means it is less reliable.